Dampak Pengembangan Objek Wisata Kawah Ijen terhadap Peningkatan Kesejahteraan Petani - WIDHIANTARI, I KADEK PUTRI; USTRIYANA, I NYOMAN GEDE; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Impact of Ijen Crater Tourism Object Development  on the Improvement of Farmer’s Welfare This study looks at the impact of Ijen Crater tourism object development on the improvement of farmer’s welfare from economic, socio-cultural and environmental aspects. The study uses proportional sampling technique with farmers as respondents and a few key informants. The study uses interactive analysis method, which consists of four steps, namely data collection, data reduction, data presentation and conclusion drawing. The result of this research show that, from the economic aspect, the development of Ijen Crater tourism object could lead to the availability of new business field. The farmers got additional income fluctuates depending on the numer of tourist visits. From the socio-cultural aspect, the development of Ijen Crater tourism object does not negatively impact the attitude of mutual helping, the preservation of traditional arts, the use of language, the level of education, the livelihood and the crime rate. From the environmental aspect, the development of Ijen Crater tourism object could lead to the increase in number and quality of tourism facilities and infrastructure, but not leading to land conversion.